Population Mobility and Infectious Disease - Apostolopoulos, Yorghos; Sonmez, Sevil; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Population Mobility and Infectious Disease Edited by Yorghos Apostolopoulos, Emory University School of Medicine, USA Sevil Sonmez, Cyprus College, Cyprus Population Mobility and Infectious Disease moves beyond traditional behavioral and demographic theories of disease diffusion to focus on larger issues of social ecology and public health. With depth rarely seen in the international literature, it explores the complex and varied roles of mobile, transient, and displaced populations in the worldwide spread of airborne, waterborne, and sexually transmitted infections. The book argues that while biomedical events cause disease, social forces such as poverty and marginalization magnify them by giving them new opportunities to take hold. Population mobility—either voluntary or forced—brings contact between populations with different disease prevalence rates; outbreaks in turn are compounded by inequalities in access to medical care. From Katrina to Darfur, and from influenza to AIDS, an expert panel of health and social scientists bring the socioeconomic context of epidemics into clear focus. -Historical perspectives on migration, development, and epidemics -Social resources and health barriers among migrant groups -The role of mobile labor populations (e.g., migrant workers, truckers, the military) in disease transmission -War, refugees, resettlement: health effects on the world scale -Natural disasters and climate change: their local and global disease impact -Leisure travel and health risks, from spring-break binges to commercial sex tourism -Methodological and design issues confronting researchers -The politics of prevention: ethical concerns in migration-related illness The unique scope of this book makes it as timely as the next health crisis and relevant to a gamut of interrelated fields, including public and international health, epidemiology, psychology, sociology, anthropology, human rights, and development and planning. By expanding concepts, examining trends, and pinpointing areas for intervention, it is a critical resource for the academic, research, practice, and policy sectors.
Demographic and Epidemiological Perspectives of Human Movement -- Demographic and Epidemiological Perspectives of Human Movement -- Key Themes Pertinent to Migration, Health, and Disease -- Population Mobility and the Geography of Microbial Threats -- Health Barriers and Inequities for Migrants -- Social Networks, Social Capital, and HIV Risks Among Migrants -- Labor Induced Migration and Disease Diffusion -- Economic Migrants and Health Vulnerability -- Military Personnel: On the Move and Vulnerable/AIDS to HIV and other STIs -- Selling Sex in the Era of AIDS: Mobile Sexworkers and STI/HIV Risks -- Tracing the Diffusion of Infectious Diseases in the Transport Sector -- Forced Migration: A Public Health Catastrophe -- War, Refugees, Migration, and Public Health: Do Infectious Diseases Matter? -- Natural Disasters, Climate Change, and the Health of Mobile Populations -- Leisure Migration and Health Concerns: A Paradox or Inevitability? -- Casual Sex in the Sun Makes the Holiday: Young Tourists' Perspectives -- In Search of the Exotic: Sex Tourism and Disease Risks -- Mapping and Modeling Disease Risk Among Mobile Populations -- Ethical and Legal Issues Impacting Migrant Health -- Migration in a Mobile World: Health, Population Mobility, and Emerging Disease.
Keywords: Public health; Public Health